2021
DOI: 10.1107/s2052252521002177
|View full text |Cite
|
Sign up to set email alerts
|

Capturing structural changes of the S1 to S2 transition of photosystem II using time-resolved serial femtosecond crystallography

Abstract: Photosystem II (PSII) catalyzes light-induced water oxidation through an S i -state cycle, leading to the generation of di-oxygen, protons and electrons. Pump–probe time-resolved serial femtosecond crystallography (TR-SFX) has been used to capture structural dynamics of light-sensitive proteins. In this approach, it is crucial to avoid light contamination in the samples when analyzing a particular reaction intermediate. Here, a method for determining a condition that avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…The crystallographic analysis of semi-stable intermediates in the water oxidation cycle also supports reaction steps coupled to rearrangement of water molecules. 22,28 Our MEP calculations suggest protonation of the Asp61 carboxylate group in an electron transfer step that is coupled to a Grotthus-type movement of three protons, with the unconventional feature of a metal ion (Mn4) acting as a relay. This single-electron-multiproton step facilitates the critical step of Mn IV -O • formation (S4') prior to O-O bond formation.…”
Section: Atomistic Scenario By Energy-path Calculationsmentioning
confidence: 90%
“…The crystallographic analysis of semi-stable intermediates in the water oxidation cycle also supports reaction steps coupled to rearrangement of water molecules. 22,28 Our MEP calculations suggest protonation of the Asp61 carboxylate group in an electron transfer step that is coupled to a Grotthus-type movement of three protons, with the unconventional feature of a metal ion (Mn4) acting as a relay. This single-electron-multiproton step facilitates the critical step of Mn IV -O • formation (S4') prior to O-O bond formation.…”
Section: Atomistic Scenario By Energy-path Calculationsmentioning
confidence: 90%
“…17,21,60,62,63 Recent room temperature and cryogenic X-ray crystallography studies favor that water access to the catalytic site occurs via the O1 channel as it shows the largest variation in water positions between studies and S states. 15,17,64 By contrast, previous theoretical studies suggested that water is delivered through the O4 channel to the Mn4 site and is inserted during the S 2 / S 3 transition via the pivot/carousel mechanism (Scheme 1C). 36,37 Recent mass spectrometric studies analyzing the oxidative damage to the D1, D2 and CP47 proteins caused by the formation of reactive oxygen species (ROS) at the Mn 4 CaO 5/6 cluster under illumination support both the B branch of the Cl1 channel and the O1 channel as water access pathways.…”
mentioning
confidence: 84%
“…In 2012, Aquila et al conducted the first TR-SFX experiments using the CFEL-ASG multi-purpose instrument at the Linac Coherent Light Source (LCLS) on the photosystem I-ferredoxin complex, where they used an Nd:YLF optical pump laser system to illuminate the complex and then probed the photo-induced structural changes that occurred within 5 to 10 µs delay times using the X-ray free electron laser [23]. This pioneering pump-probe TR-SFX experiment, accompanied by the advances in the application of pump lasers and microcrystal delivery methods, has paved the way to rapid development within the study of the structure and dynamics of light-sensitive biomacromolecules [18,24,[26][27][28]58]. In the pump-probe TR-SFX, an optical 'pump' laser is used to trigger the biochemical reaction in crystallo by illuminating the microcrystals with defined optical laser pulses at a defined wavelength and energy in a controlled region of the jet and/or nozzle before probing the reactions in crystallo with X-ray FEL pulses 'probe' at different delay times to allow observing the reaction of the biomacromolecule in real time (Figure 2) [18,23,24].…”
Section: Tr-sfx With Light-responsive Biomacromoleculesmentioning
confidence: 99%
“…The selection of the optical pump setup, e.g., the laser wavelength, fluence and pulse duration, requires careful experimental planning to achieve as high as possible excited state population while avoiding contamination, which may occur, for instance, due to the multiphoton excitation of the chromophores [15,58,61,63]. Such multiphoton excitation can lead to the propagation of radical intermediates, which obscures the biological interpretation of the TR-SFX data [63,64].…”
Section: Tr-sfx With Light-responsive Biomacromoleculesmentioning
confidence: 99%
See 1 more Smart Citation